Repeatability and Reproducibility of a Double-Pass Optical Quality Analysis Device - Xu, Chen-Chen; Xue, Ting; Wang, Qin-Mei; Zhou, Yi-Ni; Huang, Jin-Hai; Yu, A-Yong (PloS one, 2015)
To evaluate the repeatability and reproducibility of a double-pass instrument (OQASII, Visiomereics SL, Spain), which objectively measures overall optical quality of the human eyes. The right eye of 119 healthy subjects with best corrected visual acuity of 20/25 or better was included in this prospective, comparative, observational study. Two separate tests with OQASII were conducted sequentially on the same day by two different examiners. A week later, the first examiner conducted the third measurement. All subjects underwent three consecutive tests during each session. The repeatability and reproducibility of the modulation transfer function cut off frequency (MTF cutoff), the Strehl ratio, the OQAS values (OVs) at contrasts of 100%, 20% and 9%, and the objective scatter index (OSI) were analyzed. For MTF cutoff, Strehl ratio, OV100%, OV20%, OV9%, and OSI, the mean values were 39.32±9.75cpd, 0.22±0.06, 1.31±0.33, 1.33±0.39, 1.33±0.41, 0.60±0.42, respectively. Repeatability and reproducibility were good with a very low coefficient of variation and high interclass correlation coefficients (>0.88) for all parameters. Bland-Altman plots showed good correlation with 95% limits of agreement ranged from -6.04 to 6.78cpd, -0.05 to 0.05, -0.20 to 0.23, -0.29 to 0.32, -0.40 to 0.42, -0.23 to 0.21 in inter-observer, and -6.56 to 7.42cpd, -0.06 to 0.06, -0.22 to 0.24, -0.30 to 0.32, -0.35 to 0.34, -0.24 to 0.23 in inter-visit, respectively. The OQASII system yields excellent repeatability and good reproducibility for objective measurements of overall optical quality in clinic.